The consequences of shift work in family and social life - Silva, Isabel Maria Soares da (2017)
Shift work has been associated to several negative consequences for the workers. In general, it can be said that the effects on health, to some extent derived from the desynchronization between working hours and the circadian system, have been the most studied by the scientific community. On the one hand, this time arrangement, especially if it involves night hours, working on weekends and/or rotation between shifts, can have a significant negative impact on the workers’ family and social life due to the conflict between working hours and the temporal organization of family members, close friends and/or the community in general. However, under certain personal circumstances, working in a schedule different from the conventional working hours (i.e., Monday to Friday during the day) can represent advantages in this area (e.g., increased free time during the day, which can allow spending more time with small children). Compared to the effects on health, the research on the impacts of shift work with special emphasis on the social aspects has been, however, more limited. Based on literature, this chapter aims at presenting the main impacts of shift work at the family level and social life, particularly in terms ofwork-family conflict, marital relationships, parenting and participation in social/community life. In addition to the literature on the topic, empirical data from three studies carried out in Portugal, wherein the association between the lack of reconciliation of working hours/shifts with the personal and social life was evaluated, will also be presented. The chapter ends with reference to the intervention possibilities, where the role, which the organizations can play in reducing work-family conflict for these workers, is also reflected. In fact, the available evidence has indicated that workers who have non-standard working hours, including shifts, when compared with workers subjected to conventional work schedules, tend to report higher work-family conflict.